PENGARUH TINGKAT PENDIDIKAN PEMILIH PEMULA TERHADAP ANGKA GOLPUT PADA PILKADA LAMONGAN 2010 - Afnaniyati, Mir’atunnisa’ (Jurnal Review Politik, 2012)
This article is based on research about the influence of abstention of education voters inlocal election 2010 in Lamongan. This study was conducted to determine the level of education voters and the effect to educational level on points for abstaining voters in the election. With a quantitative approach that emphasizes the analysis of numerical, data (numbers) are processed with statistical method, and the studied population is 937 people and samples taken at random are 94 people. The results obtained from this study voters who are 17-year-old (adolescent) with graduate of yunior high school, have the character of an unstable and easily influenced, therefore also contribute for making decision in determining the political choice, due to the lack of political education for them.